Root xylem in three woody angiosperm species is not more vulnerable to embolism than stem xylem - Wu, Min; Zhang, Ya; Oya, Thais [UNESP]; Marcati, Carmen Regina [UNESP]; Pereira, Luciano; Jansen, Steven (Springer Nature, 2020)
Aims: Since plants are compartmentalised organisms, failure of their hydraulic transport system could differ between organs. We test here whether xylem tissue of stems and roots differ in their drought-induced embolism resistance, and whether intact roots are equally resistant to embolism than root segments. Methods: Embolism resistance of stem and root xylem was measured based on the pneumatic technique for Acer campestre, A. pseudoplatanus and Corylus avellana, comparing also intact roots and root segments of C. avellana. Moreover, we compared anatomical features such as interconduit pit membrane between roots and stems. Results: We found a higher embolism resistance for roots than stems, although a significant difference was only found for A. pseudoplatanus. Interconduit pit membrane thickness was similar for both organs of the two Acer species, but pit membranes were thicker in roots than stems of C. avellana. Also, embolism resistance of an intact root network was similar to thick root segments for C. avellana. Conclusion: Our observations show that root xylem is not more vulnerable to embolism than stem xylem, although more species need to be studied to test if this finding can be generalised. We also demonstrated that the pneumatic method can be applied to non-terminal plant samples.
Keywords: Pneumatic method; Roots; Stems; Wood anatomy; Xylem embolism resistance